Cannabis Retail Staff ("Budtenders") Attitudes Towards Cannabis Effects on Health and Experiences Interacting with Consumers – Washington State, USA. Issue 1 (1st January 2022) - Carlini, Beatriz H.; Garrett, Sharon B.; Firth, Caislin; Harwick, Robin
ABSTRACT: Cannabis legalization in Washington State has increased the availability, consumption, and potency of cannabis products for adults. Public health education promoting safe use for adult consumers has lagged behind these trends. This study assesses the potential of cannabis retail workers (budtenders) to engage in responsible use education with adult consumers at point of sale. Focus groups explored how budtenders perceive their professional role, including educating consumers about cannabis over intoxication, storage, and risks of use before driving and during pregnancy. Transcripts were analyzed to develop a coding scheme, which was then applied with an iterative review by the research team. Budtenders identified three main professional roles: creating a good experience for customers; being compliant with the state law and regulations, and educating customers on products. Budtenders did not believe their job involved discussing use during pregnancy or while driving or safe storage. They prioritized customers' autonomy over education on these topics, and they did not necessarily consider these behaviors to be harmful. Budtenders are committed to keeping minors outside stores and educating consumers on how to avoid over intoxication and exposure to cannabis contaminants. Future research could build on this to develop point-of-sale education to reduce cannabis use risks.